COMPARISON OF MATURITY OF DOMINANT SIDE AND APPENDICULAR COORDINATION OF FIVE YEARS OLD CHILDREN PRETERMS AND TERM OF THE CITY OF CASCAVEL - PR (Fiep Bulletin - online, 2014)
The weight of the newborn as well as in the gestational age has important in the prediction of future problems, related to poor nutrition of the mother, overwork during last days of pregnancy and the shortage of prenatal care. This study is justified by the worries about the impact of the prematurity condition in the course of neurodevelopmental and in the psychosocial adaptation of the child. The target was to compare the maturity of the dominant side and appendicular coordination of children preterm and term of five years old in the city of Cascavel - PR. The sample was made of 206 children selected through a gestational and social anamnesis. The sample had a comparison group of children born at term. To evaluate the lateral domain and appendicular coordination was chosen evolutionary neurological exam (Lefevre, 1972), for evaluating children of pre-school age, have been standardized in Brazilians children and for being easy to apply and interpret. Descriptive statistics for data analysis was used, the statistical program SPSS 15.0 and chi-square being adopted p ? 0.05 was used as a significance factor. There was no significant difference in the lateral dominance and appendicular coordination among children preterm and term, was not discovered relation between prematurity and appendicular coordination having a strong association between lateral dominance and appendicular coordination. The result was that the children did not show the reference pattern of Lefévre that would have the minimum of 75% of efficiency in tests. Concluding that exist a need for greater control of the motives which attack these results that the environment in which children are inserted should be investigated.
Keywords: Prematurity; Low Birth Weight; Domain Side.